Managerial and economic optimisations for prefabricated building systems - Abdallah, Ahmed (Technological and Economic Development of Economy, 2007)
This paper deals with new realisations of research, scientific development, managerial and economic optimisations – a prefabricated building systems. In the literature, all scientific fields are worked out based on efficiencies, costs, benefits, choice of execution design, technical demands, aesthetical point of view, as well as the total economics. In the present example of a school building for communities in developing countries, the following criteria have been regarded: the optimal superstructure of prefabricated concrete building systems; the particularity of developing countries (eg the climate, the political and economic conditions); the time for construction and necessary innovative developments for an economically optimised superstructure. In addition, alternative construction methods and costs for a simple but variable system which can be adapted to changing functions are suggested.Surenkamųjų pastatų konstrukcijų optimizavimas valdymo ir ekonominiu požiūriaisSantrauka. Aprašomi naujausi tyrimai, mokslinės naujovės sprendžiant surenkamųjų pastatų sistemų valdymo ir ekonominės optimizacijos klausimus. Apžvelgta literatūra, kurioje nagrinėjami efektyvumo, sąnaudų, pelno, statybos projektavimo, techninių reikalavimų, estetiniai, ekonominiai klausimai. Pateikiamas pavyzdys – mokyklos pastatas, skirtas besivystančių šalių bendruomenėms. Šiuo pavyzdžiu vertinami tokie rodikliai: gelžbetoninio surenkamojo pastato antžeminės dalies optimalumas, besivystančių šalių specifika (pvz., klimatas, politinės ir ekonominės sąlygos), statybos laikas ir reikalingi patobulinimai ekonomiškai optimaliai antžeminei daliai pastatyti. Be to, reikalingi alternatyvūs statybos metodai, taip pat turi būti kuriamos lanksčios, lengvai pritaikomos kintantiems poreikiams konstrukcinės sistemos.Reikšminiai žodžiai: statybos valdymas, ekonomika, surenkamosios sistemos, valdymo ir ekonominis optimizavimas.First Published Online: 21 Oct 2010